Pengetahuan guru bahasa Melayu tentang isi kandungan mata pelajaran dan pedagoginya (Jurnal Bahasa, 2003)
This article reports a study on the content knowledge and pedagogical content knowledge among the Bahasa Melayu teachers in the secondary schools. The purpose of this study is to (1) identify the perception of the Bahasa Melayu teachers towards their content knowledge and pedagogical content knowledge and (2) compare this knowledge by work perfomance group, gender; age, academic qualifications and work experience. Data was collected through survey using a questionnaire. This study employed stratified random sampling involving a total of 370 respondents from 108 public schools in Kedah. Statistical analyses used were descriptive and T test and AN OVA. The result revealed that most of the respondent perceived high knowledge in Bahasa Melayu but there are significant differences in their knowledge by gender, age, academic qualification and teaching experience. In conclusion, this study provide an insight into further understanding on the issues of Bahasa Melayu teachers after the implementation of English in the teaching of Science and Mathematics.